Editors' Introduction - Lindert, J.; Marsoobian, A.T. (Multidiscipl. Perspect. on Genocide and Memory, 2018)
Keywords: dept.phi

Criticism and compassion: the ethics and politics of Claudia Card - Dillon, Robin S.; Marsoobian, Armen T. (Wiley, 2018)
Criticism and Compassion: The Ethics and Politics of Claudia Card offers a unique perspective on the range of issues explored by Card during her distinguished career in philosophy. Investigates her work as an early leader in the development of feminist philosophy, challenging many preconceptions about the society’s norms regarding gender, marriage, and motherhood Crossing many disciplinary boundaries, her concept of social death has come to play a significant role in multidisciplinary field of genocide studies This volume combines many of Claudia Card’s important essays with recently commissioned essays by leading philosophers whose work has been influenced by Card The full scope of Card’s philosophy is presented here - both in her own words and those of her critics and interpreters
Keywords: dept.phi

Collective memory, memorialization and bearing witness in the aftermath of the Armenian Genocide - Marsoobian, Armen T. (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This chapter describes and analyzes an ongoing project of memorialization of the Armenian Genocide in Turkey. It explores the importance of memorialization for collective historical memory, especially in situations where historical memory has been subverted by genocide denial. Among many aspects of memorialization, its role in bearing witness is explored and highlighted. Three components of the memory project are described: (1) the photography exhibitions, (2) the publications, and (3) the creation of memory sites. The project centers on the story of the Dildilian family in Ottoman Turkey before, during, and after the genocide, covering the years 1872–1923. A microhistory of the life of the Armenian minority is chronicled by means of the personal memories and stories of members of the family. The history is richly illustrated with photographs and drawings that serve as the basis of the photography exhibitions and books. Exhibitions and associated talks and panels have taken place in Istanbul, Merzifon, Diyarbakir, and Ankara. The chapter describes and analyzes the reaction of the Turkish public to the project.
Keywords: Armenian Genocide; Bearing witness; Collective memory; Genocide denial; Memorialization; Turkey; dept.phi

How do we memorialize genocide? The case of the German memorial to the murdered Jews of Europe - Marsoobian, Armen T (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This book explores the memory and representation of genocide as they affect individuals, communities and families, and artistic representations. It brings together a variety of disciplines from public health to philosophy, anthropology to architecture, offering readers interdisciplinary and international insights into one of the most important challenges in the 21st century. The book begins by describing the definitions and concepts of genocide from historical and philosophical perspectives. Next, it reviews memories of genocide in bodies and in societies as well as genocide in memory through lives, mental health and transgenerational effects. The book also examines the ways genocide has affected artistic works. From poetry to film, photography to theatre, it explores a range of artistic approaches to help demonstrate the heterogeneity of representations. This book provides a comprehensive and wide-ranging assessment of the many ways genocide has been remembered and represented. It presents an ideal foundation for understanding genocide and possibly preventing it from occurring again
Keywords: Aesthetics; Counter-monument; Health Psychology; Health psychology; History of World War II and the Holocaust; Holocaust; James E. Young; Jochen Gerz; John Dewey; Marian Marzynski; Memorial to the Murdered Jews of Europe; Memorial to the murdered jews of europe; Modernism; Noël Carroll; Peter Eisenman; Public Health; Public health; Public memorials; Sociology; Sociology, general; World War, 1939-1945; dept.phi

The suppression of cultural memory and identity in Bosnia and Herzegovina - Pettigrew, David (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This chapter identifies an orchestrated effort in “Republika Srpska”—an entity within Bosnia and Herzegovina that was recognized by the 1995 Dayton Peace Agreement − that is designed to prevent survivors of the genocide from erecting memorials to the victims in such locations as Višegrad, Prijedor, and Foča. While memorials for victims have been prohibited, and survivors have been prevented from using the term “genocide,” memorials to the perpetrators have been installed in the center of Višegrad, and near the Trnopolje concentration camp in Prijedor Municipality. In the hills above Sarajevo, in a location from which the city’s residents were attacked during the siege, a plaque honoring indicted war criminal Ratko Mladić has been installed. Accordingly, this chapter considers the extent to which the discriminatory practices regarding memorials in Republika Srpska constitute a violation of human rights. Further, the chapter argues that, following Raphael Lemkin’s definition of genocide, the prohibitive policies in Republika Srpska with respect to memorials and commemorative practices constitute nothing less than a continuation of the genocide, a second phase of the genocide designed to ensure the permanent erasure of a world that was destroyed. These human rights violations and the continuation of the genocide are a troubling testament to the failure of the international community in Bosnia, and to the problematic legacy of the Dayton Peace Agreement.
Keywords: Apartheid; Cultural memory; Dayton Peace Agreement; Dayton peace agreement; Health Psychology; Health psychology; History of World War II and the Holocaust; Human rights; Prohibited memorials; Public Health; Public health; Raphael Lemkin; Sociology; Sociology, general; World War, 1939-1945; dept.phi